TINJAUAN EFISIENSI SALURAN IRIGASI PADA JARINGAN UTAMA DAERAH IRIGASI LOMAYA - Madjid, Muthmainna Abdul; Yusuf, Barry; Husnan, Rawiyah (Composite Journal, 2023)
The primary problem in a region with limited water resources is the use of irrigation water and this limited water resource is associated with water volume losses in the irrigation channel, particularly in the primary, secondary, and tertiary channels through evapotranspiration, infiltration, and seepage. Therefore, the irrigation channel reguires effective and efficient management. The objective of this study is to evaluate the efficiency of Lomaya Irrigation Area to denote water use and to maximize the water use for agriculture. This study is conducted by applying field data in the primary channel of Lomaya Irrigation Area and data from the climatology of Bolango Bone Tumbihe Watershed. The data collected are a wet cross-sectional area of channel and flow speed in several vertical points. The average daily evaporation rate and water losses in the primary channel of Lomaya Irrigation Area are determined by employing Penman evaporation method. In addition, the efficiency value is obtained by comparing inflow and outflow debit in the irrigation channel. The result of water losses value analysis in the Lodelombongo irrigation channel due to evaporation is 5,14 m³/sec, and the value is not too influential for the water losses in the channel compared to the water losses due to leakage in the channel. In the meantime, the average efficiency value in the Lodelombongo irrigation channel is 61%, where it is no longer in compliance with the predetermined provision in the irrigation planning criteria. The greatest efficiency value in primary channel BLI-BL2 is 92,42%, whereas the smallest value in the primary channel BL3-BL.BI is 49,35Y%, the greatest efficiency value in secondary channel BL.B3-BL.B4 is 72,64%, whereas the smallest value in the secondary channel BL.BS-BL.B6 is 43,89%. The efficiency value is affected by water volume, which losses on its way where the water losses in the irrigation channel encompass water losses components through evapotranspiration, percolation, seepage, and leakage.